Contaminated Soils, Sediments and Water Volume 10 Successes and Challenges - Calabrese, Edward J.; Kostecki, Paul T.; Dragun, James (Springer US : Imprint: Springer, 2006)
Contaminated Soils, Sediments and Water: Successes and Challenges, Volume 10 contains a valuable collection of success stories (and challenges) in the areas of environmental fate, heavy metals, modeling, MTBE and oxygenates, regulatory, remediation, risk assessment, site assessment and sampling methodology. It demonstrates the progress that has been made in working together toward the optimization of established approaches, as well as embracing departures from traditional regulatory models in order to address the threats to our natural resources. The book is divided into eight sections: Part I: Environmental Fate; Part II: Heavy Metals; Part III: Modeling; Part IV: MTBE and Oxygenates; Part V: Radionuclides; Part VI: Regulatory; Part VII: Remediation; Part VIII: Risk Assessment and Remedial Approaches Towards Restoration and Management of Contaminated Rivers. Contributing authors to Contaminated Soils, Sediments and Water: Successes and Challenges, Volume 10 are from government agencies, academic institutions, the consulting community and industrial companies. They document the state of environmental science and provide perspective on the progress that has occurred.